2017
DOI: 10.1080/14786419.2017.1344660
|View full text |Cite
|
Sign up to set email alerts
|

Two new protostane-type triterpenoids from Alisma orientalis

Abstract: Two new protostane-type triterpenoids, 17-epi alisolide (1) and 24-epi alismanol D (2), were isolated from Alisma orientalis together with one known compound. Their structural elucidations were conducted by NMR, UV and HRESIMS spectroscopic analyses, and comparison with the literature data. All the isolated compounds were evaluated for inhibitory effects on HCE-2. Compound 2 displayed moderate inhibitory activity against HCE-2 with IC value of 23.1 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Protostane triterpenes are natural plant products with distinct pharmacological activities, but their natural distribution is limited to a few plant families 33,34 . Squalene epoxidase (SE) is the rate-limiting enzyme in the triterpene biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Protostane triterpenes are natural plant products with distinct pharmacological activities, but their natural distribution is limited to a few plant families 33,34 . Squalene epoxidase (SE) is the rate-limiting enzyme in the triterpene biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016 and 2017, Ma et al identified a library of new alisol derivatives, namely, alismanols M ( 24 ) and O‐Q ( 25–27 ), 16‐oxo‐11‐anhydroalisol A 24‐acetate ( 28 ), 13 β ,17 β ‐epoxy‐24,25,26,27‐tetranor‐alisol A 23‐oic acid ( 29 ), 16 β ‐acetoxy alisol B ( 30 ), and 16 α ‐acetoxy alisol B ( 31 ) from A. orientale (Cang et al, 2017; Huang et al, 2017; Ma et al, 2016). Furthermore, Xin et al isolated two new protostanes, 17‐ epi alisolide ( 32 ) and 24‐ epi alismanol D ( 33 ), from A. orientale (Xin et al, 2018). Li et al also investigated A. orientale and identified 12 new triterpenes, including alisol R ( 34 ), 25‐methoxyalisol F ( 35 ), 16 β ‐hydroperoxyalisol B 23‐acetate ( 36 ), alisol S 23‐acetate ( 37 ), 16 β ‐hydroperoxyalisol B ( 38 ), 16 β ‐methoxyalisol B ( 39 ), 16 β ‐methoxyalisol E ( 40 ), 16 β ,25‐ dimethoxyalisol E ( 41 ), 16 β ‐hydroperoxyalisol E ( 42 ), alisol T ( 43 ), and two natural triterpenoids alisols U ( 43 ) and V ( 44 ).…”
Section: Phytochemical Constituents Of the Genus Alismamentioning
confidence: 99%
“…5 β ,29‐Dihydroxy alisol A ( 59 ), obtained from A. orientale , inhibited CES 2 with an IC 50 value of 29.2 μM, and the underlying mechanism between 59 and CES 2 was studied by molecular docking, all of which revealing the presence of hydrogen bond interactions with Glu77, Ser80, IIe446, and Lys447 and a lowest binding free energy of −3.94 kcal/mol (Wang et al, 2019). Xin et al (2018) isolated two protostanes 17‐ epi alisolide A and 24‐ epi alismanol D ( 33 ) and found that 24‐ epi alismanol D ( 33 ) had an inhibitory effect against CES 2 with an IC 50 value of 23.1 μM. Twenty‐two protostanes were obtained from A. orientale by Mai et al, and the inhibitory effect of all the compounds on CES 2 was experimentally evaluated.…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…Among C-2 may be submitted by carbanyl group (109) (Mai et al, 2015). The configuration of C-17 is determined (107, 108) (Xin et al, 2018).…”
Section: Nor-and Seco-protostanesmentioning
confidence: 99%